Analisis Kelayakan Muatan PAI pada Film Animasi Nussa dan Rara serta Pemanfaatannya Sebagai Sumber Belajar di Sekolah Dasar - Ramadhani, Annisa; Khadijah, Siti; Ghofur, Abdul (Lembaga Publikasi Ilmiah Universitas Islam Bunga Bangsa Cirebon, 2024)
The rapid development of technology today makes educational institutions must improve to keep up with the times. Learning media must be made technology-based in accordance with current developments. Nussa and Rara Animation Film is an educational film based on Islamic religious education that is widely used in various Elementary Schools. The purpose of this study was to analyze the feasibility of PAI content in the animated film Nussa. This thesis also discusses the utilization of PAI content in Nussa and Rara animation as a learning resource in Elementary Schools. This research was designed with a qualitative research model, the instruments used in this research used observation sheets and transcription techniques. The episodes to be analyzed are